A Poor Prognostic Case of Mucoepidermoid Carcinoma of the Thyroid: A Case Report. (30th August 2012) - Shindo, Koji; Aishima, Shinichi; Okido, Masayuki; Ohshima, Akira
Abstract : Mucoepidermoid carcinoma (MEC) of the thyroid is very rare and low-grade indolent neoplasm. In past reports of the thyroid MEC, only seven cases were described as poor prognosis. A 91-year-old woman presented with a rapidly growing mass of the left upper neck. She was followed thyroid papillary carcinoma (PC) without operation for two years. Fine needle aspiration cytology (FNAC) showed undifferentiated cells. Total thyroidectomy and bilateral neck dissection were performed. In pathological findings, the tumor had two areas of MEC and PC. The boundary of them was mixed. She died of multiple lung metastases only after four months from the operation. We report a rare case of thyroid MEC which had an aggressive behavior and poor prognosis. This case is a precious in that thyroid MEC occurred during observation of PC and suggests a possibility of the transformation from PC to MEC.